Transient Receptor Potential (TRP) Ion Channels Involved in Malignant Glioma Cell Death and Therapeutic Perspectives - Lefranc, Florence (Frontiers in Cell and Developmental Biology, 2021)
Among the most biologically, thus clinically aggressive primary brain tumors are found malignant gliomas. Despite recent advances in adjuvant therapies, which include targeted and immunotherapies, after surgery and radio/chemotherapy, the tumor is recurrent and always lethal. Malignant gliomas also contain a pool of initiating stem cells that are highly invasive and resistant to conventional treatment. Ion channels and transporters are markedly involved in cancer cell biology, including glioma cell one. Transient receptor potential (TRP) ion channels are calcium permeable channels implicated in Ca2+ changes in multiple cellular compartments by modulating the driving force for Ca2+ entry. Recent scientific reports have shown that these channels contribute to the increase in glioblastoma aggressiveness, with glioblastoma representing the ultimate level of glioma malignancy. The current review focuses on each type of TRP ion channel potentially involved in malignant glioma cell death, with the ultimate goal of identifying new therapeutic targets to clinically combat malignant gliomas. It thus appears that cannabidiol targeting the TRPV2 type could be such a potential target.